STRATEGI AKUMULATIF DALAM STRUKTUR INFORMASI PADA BAGIAN PENDAHULUAN ARTIKEL PENELITIAN DALAM BAHASA INGGRIS - NK Mirahayuni (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2014)
This research into English research articles (RAs) produced by native English writers focuses on the organization of information (or news) in the Introduction section. Specifically it focuses on the information organization in a paragraph and between paragraphs of the section. The study investigates the news structures inside a paragraph as well as those between paragraphs in the section. The study involves ten (10) internationally published journal articles. The results indicate a general tendency for the new information in the native English RA Introductions to be organised and presented in an accumulative strategy, and the accumulation may be achieved in various ways. The study is hoped to shed lights and insights for the non-native English researchers who aim for international publication, in how they may organize their research reports.